Morphological Characteristic of Apple Velvet (Diospyros blancoi) at Germplasm Garden of LIPI Cibinong Collection - Puspita Deswina; Novia Delliasari Aliyya Az Zahra; Etty Hesthiati Hesthiati (Talenta Publisher, 2019)
Apple velvet (Diospyros blancoi) is one of the local fruits which classified as a rare planteven it has high economic value. Apple velvet has various morphology that needsselection from any various characters to identify the most superior character and hashigh potential to be developed. The analysis of diversity from one population can beidentified to know the morphology character from the plant. The commonly usedcharacteristics include tree trunks, leaves, flowers, fruits, and seeds. This study wasconducted using the quantitative and qualitative methods the result of the characterizedplants showed that the apple velvet plants in Germplasm Collection Garden of LipiCibinong have the average height between 3.5-15 m, stem diameter between 14.1-72.29cm has no shapes of leaves such as oval and wide oval. White flower crown, 2 shapes offruits such as round and oval pattern, 2 shapes of seeds such as elliptic and biconvex.Keywords: apple velvet plants, characterization, rare plant